The Composition and Function of Intestinal Microbiota Were Altered in Farmed Bullfrog Tadpoles (Aquarana catesbeiana) during Metamorphosis - Xiaoting Zheng; Qiuyu Chen; Xueying Liang; Vikash Kumar; Alfredo Loor; Hongbiao Dong; Chang Liu; Jinlong Yang; Jiasong Zhang (Microorganisms, 2024)
The bullfrog Aquarana catesbeiana is one of the main farmed frog species in China, with a low overall survival of farmed bullfrogs from hatching to harvest since bullfrog tadpoles are fragile during the metamorphosis period. The intestinal bacterial community can play crucial roles in animal development; however, little is known about the alteration of the gut microbial community of A. catesbeiana during metamorphosis. The present study used 16S rRNA amplicon sequencing to investigate the intestinal bacterial community in A. catesbeiana at four distinct developmental stages. Moreover, we determined the bullfrog’s body morphological parameters and the intestine histology at different developmental stages. The results showed a reduction in the total length and snout–vent length of A. catesbeiana during metamorphosis. The intestinal microbial composition of A. catesbeiana exhibited variation throughout the process of metamorphosis. The terrestrial stage showed shifts in the bacterial composition compared to the aquatic stages, including a reduction in Bacteroidetes and an increase in Firmicutes. Furthermore, the presence of Prevotella, Bifidobacterium, Leucobacter, Corynebacterium, Bulleidia, Dorea, Robinsoniella, and Clostridium in A. catesbeiana metamorphosis appears to be mainly related to the host’s epithelial cells’ height and total body mass. The results indicated that the intestinal microbial composition changed with the bullfrog–tadpole metamorphosis. The genera of Prevotella, Bifidobacterium, Leucobacter, Corynebacterium, Bulleidia, Dorea, Robinsoniella, and Clostridium might be potential probiotics.